2017
DOI: 10.1063/1.4986146
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-resolution depth-resolved measurement of florescence-yield soft x-ray absorption spectroscopy for FeCo thin film

Abstract: We develop a fluorescence-yield depth-resolved soft x-ray absorption spectroscopy (XAS) technique, which is based on the principle that the probing depth is changed by the emission angle of the fluorescence soft x rays. Compared with the electron-yield depth-resolved XAS technique, which has been established in this decade, we can observe wider range in-depth XAS distribution up to several tens of nm. Applying this technique to a 30 ML (∼4.3 nm) FeCo thin film, we observe Fe L-edge XAS spectra at the probing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Co 3 O 4 , which has the highest oxidation state, has a higher energy peak position at approximately 780 eV, corresponding to Co 2p 3/2 (L 3 edge), compared with Co and CoO, whose peak positions are at approximately 779 eV. These spectra are well-known in previous studies, but we obtained the Co, CoO, and Co 3 O 4 data shown in Figure by using the same beamline configuration as wavelength-dispersive XAS. Therefore, the measured spectrum can be estimated by how much oxidation proceeds as fitted using these spectra by obtaining the ratio of these reference spectra.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Co 3 O 4 , which has the highest oxidation state, has a higher energy peak position at approximately 780 eV, corresponding to Co 2p 3/2 (L 3 edge), compared with Co and CoO, whose peak positions are at approximately 779 eV. These spectra are well-known in previous studies, but we obtained the Co, CoO, and Co 3 O 4 data shown in Figure by using the same beamline configuration as wavelength-dispersive XAS. Therefore, the measured spectrum can be estimated by how much oxidation proceeds as fitted using these spectra by obtaining the ratio of these reference spectra.…”
mentioning
confidence: 67%
“…Recently, to extend the range of applicable gas pressures, the detection of fluorescence soft X-rays has been realized by using a fluorescence X-ray imaging system, and this method enabled observation of the surface chemical reactions under a gas pressure of ca. 100 Pa. On the other hand, nondestructive depth-resolved XAS measurements, which have a resolution of less than 1 nm to analyze the depth profile of the chemical status in the near-surface region, have already been developed . However, depth-resolved analysis in real time has not been actualized as a simultaneous measurement, which can follow a chemical reaction on a material surface that proceeds in the depth direction with processing time.…”
mentioning
confidence: 99%
“…The wavelength (λ) was estimated from the attenuation length ( l ) and detection angle using the following relation: λ = l sin θ d . 45 The lowest θ d was determined to be ∼0.1°. By analyzing a set of X-ray data recorded at different wavelengths, depth-resolved XAS and XMCD spectra can be obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Si-PMs (or MPPCs [1]) have an advantage in fabricating a pixelated detector operated in a low voltage, comparing with MCPs. Observation of spin structure in a magnetic thin film is planned with the fluorescence-yield depth resolved XAS technique [2]. In this method, a two-dimension pixelated detector for soft X-ray region is much useful.…”
Section: Introductionmentioning
confidence: 99%